The Ergative Morphosyntax in Danuwar - Chaudhary, Mahesh Kumar (JODEM: Journal of Language and Literature, 2019)
This article is an attempt to analyse ergativity in Danuwar clauses. It is organized into four sections. First section provides the theoretical background where attempts are made to explain the concept of ergativity. The next section deals with the morphology of ergativity in Danuwar. Then after, efforts are made to analyse the syntax of ergativity in the language in terms of constituent order, transitivity, verb agreement, control site, case demotion, and coordinate construction. Finally, the main findings of the paper are summarized.